Avaliação do extrato de Momordica charantia em Salmonella typhimurium: Mutagenicidade e antimutagenicidade - Varella, Soraya Duarte [UNESP]; Gonçalves, Eliana Ribeiro [UNESP]; Biella, Carlos Alexandre [UNESP]; Varanda, Eliana Aparecida [UNESP]; Do Sacramento, Luis Vitor Silva [UNESP] (My University, 2001)
In the last years some natural products has been described as supressors of the mutagenic process in bacteria, the antimutagenics. The literature reference that in most of the countries, the population makes use of medicinal plants. The plant Momordica charantia (Cucurbitaceae) is original from Africa being used popularly as purgative, antirheumatic and for skin problems, burns and hemorrhoids. The present work had as objective to evaluate the mutagenic and antimutagenic activities of the ethanolic extract of M. charantia in Salmonella/microsome assays using TA100, TA98 and TA102 strains. It was verified that the extract did not present mutagenic activity when evaluated in different concentrations (0.64, 1.27, 2.55 and 3.84 mg/plate) but acted as antimutagenic agent against the mutations induced by the sodium azide (TA100,-S9), 4-nitro-phenylenediamine (TA98, -S9), daunomycin (TA102, +S9) 2-anthramine (TA100 and TA98, +S9) and 2-aminofluorene (TA102, +S9). When the metabolic activation (+S9) was used, the percentage of inhibition of the mutagenicity varied in the range of 31%-96%, while in absence of metabolizing system (-S9), the maximum percentage of inhibition of the mutagenicity was 44%. In that way, we can conclude that the metabolites found in the extract has potential to protect the genetic material against the damages induced by different chemical agents.
Evaluation of the Momordica charantia extract in Salmonella typhimurium: Mutagenicity and antimutagenicity
Keywords: Ames test; Antimutagenic activity; Momordica charantia; S. typhimurium; 2 aminoanthracene; 2 fluorenylamine; 4 nitro 1,2 phenylenediamine; antimutagenic agent; antirheumatic agent; bacterial antigen; daunorubicin; laxative; Momordica charantia extract; mutagenic agent; sodium azide; antineoplastic activity; burn; concentration response; controlled study; evaluation; hemorrhoid; inhibition kinetics; medicinal plant; metabolic regulation; metabolite; microsome; momordica charantia; mutagenicity; nonhuman; phytotherapy; plant; Salmonella typhimurium; skin disease; strain identification